The afternoon counter-electrojet current system along the 75°E meridian during the IEEY - Bhardwaj, S. K.; Subba Rao, P. B. V. (My University, 2017)
In the present study, the technique of principal component analysis (PCA) is applied to analyze the hourly mean values of geomagnetic feld components D, H, and Z along an Indo-Russian chain of stations during the International Equatorial Electrojet Year (IEEY) from January 1992 to June 1993. This technique (PCA) is found to be suitable for separating the normal electrojet (NEJ) and counter-electrojet (CEJ) variations, and the frst two principal components (PCs) are able to describe the characteristics of NEJ- and CEJ-related feld variations. It is found that the frst principal component (PC-1) for H, D, and Z varies as a function of time with latitude and depicts the well-known Sq variations, whereas PC-2(H) does not show any variations at all latitudes during NEJ days. On CEJ days, PC-2(H) shows a large negative excursion at equatorial stations (KAN to BAN). The NEJ- and CEJ-related current systems are determined by combining the hourly inequalities in D and H. PC-1 brings out a well-defned anticlockwise loop for NEJ days, with its focus near the dip latitude (~35Â°N), and a clockwise loop for CEJ days with a well-defned focus near the dip latitude (~20Â°N) around noon local time. The CEJ-related current system is marked by intense westward current fow in the equatorial belt and is shown to close its path by forming a clockwise loop extending from the dip equator to midlatitudes. Comparison with a numerically simulated current system, caused by various tidal modes, emphasizes the signifcance of antisymmetric semidiurnal tidal modes in the generation of CEJ events.
Keywords: Counter electrojet; Principal component analysis; Tidal winds; Sq variations